(2+w)=w2+(w+1)

Since w is on the right side of the equation, switch the sides so it is on the left side of the equation.

w2+w+1=2+w

Subtract w from both sides of the equation.

w2+w+1-w=2

Combine the opposite terms in w2+w+1-w.

Subtract w from w.

w2+0+1=2

Add w2 and 0.

w2+1=2

w2+1=2

w2+1=2

Subtract 1 from both sides of the equation.

w2=2-1

Subtract 1 from 2.

w2=1

w2=1

Take the square root of both sides of the equation to eliminate the exponent on the left side.

w=±1

Any root of 1 is 1.

w=±1

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

w=1

Next, use the negative value of the ± to find the second solution.

w=-1

The complete solution is the result of both the positive and negative portions of the solution.

w=1,-1

w=1,-1

w=1,-1

Solve for w (2+w)=w^2+(w+1)